(untitled) (Biological Sciences - PJSIR, 1998)
The triglycerides separated from Citrullus vulgaris seed oil were fractionated by silver nitrate impregnated thin layer chromatography into six fractions with respect to their degree of unsaturation, The composition and nature of the fatty acids at their 0<,0<’ and P-position was determined by the use of pancreatic lipase and gas chromatography,The unsatur- ated CIS acids occupy the P-position depending upon the comparatively higher percentage of the respective acid.